2019
DOI: 10.2478/revecp-2019-0003
|View full text |Cite
|
Sign up to set email alerts
|

The determinants of consumer behaviour of students from Brno when purchasing organic food

Abstract: The subject of this paper is the analysis of consumer behaviour in the organic market, focused on the behavior of students from Brno. Our study brings information which can potentially be used for further research and will also be useful for organizations with a practical interest in the production sale and distribution of organic food. To investigate the influence of the various factors was used the extended model of Theory of Planned Behaviour (TPB). In the current concept, there is no research in the Czech … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
1
6
0
2
Order By: Relevance
“…The reasons for choosing organic food most often mentioned in the literature indicate health aspects, i.e., not modifying food, not saturating it with chemicals and preservatives, and presenting overall high health values [35,52,53]. The obtained results relate, among others, to Czech consumers, which have been confirmed in national surveys [54]. They demonstrated that better flavor, health concerns, and food freshness were the most important attributes influencing the decision-making of the young Czechia consumer.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The reasons for choosing organic food most often mentioned in the literature indicate health aspects, i.e., not modifying food, not saturating it with chemicals and preservatives, and presenting overall high health values [35,52,53]. The obtained results relate, among others, to Czech consumers, which have been confirmed in national surveys [54]. They demonstrated that better flavor, health concerns, and food freshness were the most important attributes influencing the decision-making of the young Czechia consumer.…”
Section: Discussionsupporting
confidence: 66%
“…Similar barriers were indicated by French and Spanish consumers [30,43], and also by Asian consumers [64,65]. However, Švecová and Odehnalová [54], in studies conducted among young Czech consumers, showed that young consumers are willing to pay far higher prices for good-quality food, and as a result the high price no longer acts as one of the main barriers in the purchase of organic food. Around 90% of respondents were willing to pay a higher price.…”
Section: Discussionmentioning
confidence: 62%
“…Overall, the clear lack of consensus with respect to the relationship between health, environmental and ethical concerns and purchase behavior (Yogananda Auroomooga and Nair 2019;Svecova and Odehnalova 2019;Shukla 2019) makes it difficult to design and assess marketing strategies to encourage pro-health, pro-environment or ethical purchasing behaviors. This study aims to fill the research gap by bringing together empirical evidence for the association between health, environmental and ethical concerns and consumer purchase behavior through meta-analysis and narrative review.…”
Section: Introductionmentioning
confidence: 99%
“…Another interesting finding in the literature is in the area of ethical consumerism, organic products, and sustainability. A study found that young students in Brno are willing to pay a premium for the freshness and better taste of organic products as well as the associated quality and are positively inclined to information relating to the moral and health issues associated with this purchase type (Švecová and Odehnalová, 2019). This is interesting to note, especially when compared to the commonly reported findings around ethical consumerism which tends to suggest somewhat different behaviour patterns from young consumers.…”
Section: Figure 11 Major Influences On Consumer Decisionsmentioning
confidence: 87%